MANFAAT PEMBINAAN BAGI NARAPIDANA SAAT MENJALANI PIDANA PENJARA - Petrus Irwan Panjaitan (to-ra, 2017)
Abstract Consumer nancing business in the form of Credit Card as a form of less cash society is developing in Indonesia has even become a culture in modern society coupled with the support of fast payment system, safe, ef cient and reliable, smoothness in payment, providing legal certainty for the community in doing transaction, but consumer nance business though very attractive but does not mean this business has no risk at all, as credit giving, the risk will still exist at the time of stalled payment of credit card arrears by consumers. In the event of a consumer credit crunch, banks usually use debt collection services known as debt collectors. Often debt collectors in doing debt collection services work unprofessionally even sometimes tend to do acts against the law, so it will cause harm to customers and credit card issuing bank, because it is not in accordance with what is expected. Keywords: payment system; Credit Card; debt collectors; accordance.